Proposal for an Urgency Score as General Referral Strategy to Second- Care Rheumatology - Mohamed Omar Ghazal; Michael Schirmer (Annals of Musculoskeletal Medicine - Peertechz Publications, 2017)
Objectives: To assess the practicability of a questionnaire to routinely discriminate between urgent and non-urgent rheumatology appointments by administrative personnel. Second, to discuss the results in view of current literature on referral strategies of rheumatic patients from primary to secondary care, including those with immune-mediated rheumatic diseases. Methods: In our rheumatology unit a rheumatology urgency score (RUS) is calculated on the basis of a multi-dimensional questionnaire with fi ve main domains: Administrative information (referral mode, subjective urgency), clinical signs, time of maximal symptom presentation, available laboratory and imaging fi ndings. This RUS has been routinely used by administrative personnel and nurses since July 2013 for assigning appointments at initial consultation, with urgency defi ned as RUS ≥ 4 points. Anonymous score sheets including the time until appointment assignment were retrospectively analyzed. A literature search was performed with last update in January 2015 to identify previous evidence for effective strategies reducing waiting times and underlying causes for prolonged waiting times. Results: Consecutive questionnaires from 153 patients were analyzed, with RUS ≥ 4 points considered as urgent for 75% of the patients (n = 115). Based on the bimodal distribution curve of waiting times, the total cut-off between short and long waiting times was defi ned as 23 days. Mean waiting time for urgent patients was shorter with 14.4 days (±13.1 days), than for non-urgent appointments with 24.6 days (±15.4 days) (p<0.001). 27.5% of all appointments were assigned independently from RUS, with 40.5% of questionnaires with RUS < 4 resulting in a fast appointment and 16.1% of questionnaires with RUS ≥ 4 points resulting in a slow appointment. Without these incorrect assignments, waiting times were shorter for urgent than for non-urgent patients with 8.6 and 38.0 days, respectively (p<0.001). Administrative information, clinical signs, time of maximal symptom presentation, laboratory and imaging fi ndings were available in 99.3%, 94.1%, 77.1%, 33.3%, and 17% of the questionnaires, respectively. According to the literature, effective strategies resulting in a reduction of referral delay are rapid access services, early arthritis clinics, triage of referrals with use of referral forms and educational programs for primary care physicians. A general strategy for all patients including those with immunemediated rheumatic diseases like RUS has not been presented so far. Conclusion: The rheumatology urgency score resulted in a bimodal distribution of waiting times, thus distinguishing between urgent- and non-urgent appointments. To achieve better quality in differentiation of urgent appointments, administrative personnel and nurses have to be further instructed and motivated.In the future, RUS has to be further validated in a prospective approach taking into account the subjective and objective physicians' feed-back of urgency and fi nal diagnoses.